Composites of CoFe2O4/Graphene oxide/Kaolinite for adsorption of lead ion from aqueous solution - Daniel Reta, Yared; Desissa, Temesgen Debelo (Frontiers in Materials, 2023)
In this work, we established composites from kaolinite (K), CoFe2O4 (CF), and graphene oxide (GO) for the adsorption of the lead ion (Pb (II)). Initially, a composite of CF-GO was synthesized by hydrothermal method using cellulose bio-template extracted from false banana.The weight ratio of i.e., CF/(x) GO (x =0.20, 0.25, 0.30). The sample with x = 0.30, i.e., CF-0.3GO exhibited a better adsorption capacity of about 23.6 mg g -1 from the binary composite samples at the initial Pb concentration of 50 mg L -1 . Then, the contact time and adsorbent dosage of CF-0.3GO were optimized with the corresponding results of 90 min and 1.2 g L -1 , respectively. A ternary composite was formulated from the sample of CF-0.3GO and Kaolinite (K) with the nominal composition of (1-y)K/(y)(CF-0.3GO), where y = 0.30, 0.45, 0.60, and 0.75. Among the ternary composites, the sample with a composition of 0.25K/0.75(CF0-0.3GO) showed the best adsorption capacity of about 4.2 mg g -1 at the initial Pb concentration of 10 mg L -1, and this sample was subsequently selected for further studies. The synthesized composites were characterized using powder X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transforms infrared spectroscopy (FTIR), and Differential thermogravimetric analysis (TGA-DTA), respectively, to determine phase purity, the particles morphology, functional groups, and thermal stability of samples. Atomic absorption spectroscopy (AAS) was used to determine the adsorption capacity of samples. The effect of pH ranging from 2-10 was investigated for the present composite. At pH of 4, the adsorption capacity and removal efficiency changed significantly, with the corresponding results of 6.62 mg g -1 and 99 %, respectively, and becomes constant.Adsorption kinetics were studied for the composite with the composition of (0.25K/0.75[(CF-0.3GO)]) and the kinetic behavior obeyed the Pseudo-second-order adsorption kinetics. The Freundlich isotherm model best fits the adsorption isotherm, with a correlation coefficient of 0.93. Finally, the synthesized composite was stable for three-round tests toward the Pb(II) removal. Therefore, the results of this study indicate that the composites of CoFe2O4/Graphene oxide/Kaolinite could be a potential candidate for the removal of Pb (II) ions.